Effect of Using Aqueous extract of Chamomile Flowers on the Level of Glucose and Total protein in Blood Serum of Broilers Exposed to Heat stress (Journal of Hama University, 2022)
The research was performed on 120 broiler chickens in order to study the effect of using different concentrations of aqueous extract of chamomile flowers in alleviating the effects of heat stress, by conducting a study of the level of glucose and total protein in their blood serum. The broilers from the age of 1-42 days were raised in a private poultry farm. At the age of 28 days, they were divided into four groups: the first group was not exposed to heat stress and was not given the extract, while the remaining three groups (the second, third and fourth) were exposed to Heat stress at 32±2°C for 2 hours per day until the end of the experiment at age of 42 days, the second group was not given the extract, while the third group was given water containing the extract in a concentration of 0.9% and the fourth group was given water containing the extract in a concentration of 1.2% in drinking water. Blood samples were taken at the age of 42 days. The results showed a significant increase in the level of glucose with a significant decrease in the level of total protein in the blood serum of broilers of the second group in comparison with the first group. While giving of the extract in concentrations of 1.2% and 0.9% to the third and fourth groups led to a significant decrease in the level of glucose with a significant increase in the level of total protein in blood serum in comparison with the second group, without significant differences between the third and fourth groups. The results also showed that the level of glucose and total protein in broilers of the first group was less than their levels in the third and fourth groups. The results showed a possibility of using the aqueous extract of chamomile flowers in alleviating the effects of heat stress in broilers by comparing the levels of glucose and total protein in the blood serum between the groups that were given the extract and those that were not, and the best results were recorded in the fourth group which was given water containing the aqueous extract in a concentration of 1.2%.